1992
DOI: 10.1093/carcin/13.10.1789
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 2E1 and 2A6 enzymes as major catalysts for metabolic activation of N-nitrosodialkylamines and tobacco-related nitrosamines in human liver microsomes

Abstract: An acetyltransferase-overexpressing strain of Salmonella typhimurium (NM2009) has been used to investigate roles of human liver microsomal cytochrome P450 (P450) enzymes in the activation of carcinogenic nitrosamine derivatives, including N-nitrosodialkylamines and tobacco-smoke-related nitrosamines, to genotoxic products. Studies employing correlation of activities with several P450-dependent monooxygenase reactions in different human liver samples, inhibition of microsomal activities by antibodies raised aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
181
0
4

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 348 publications
(190 citation statements)
references
References 0 publications
5
181
0
4
Order By: Relevance
“…CYP2E1 antibody (50 g), SKF 525-A (1 mM), and disulfiram (25 M) were also used as controls to ascertain the role of CYP2E1. Details were essentially similar to those for the erythromycin N-demethylation assay published previously (28,63,64).…”
Section: Methodsmentioning
confidence: 96%
“…CYP2E1 antibody (50 g), SKF 525-A (1 mM), and disulfiram (25 M) were also used as controls to ascertain the role of CYP2E1. Details were essentially similar to those for the erythromycin N-demethylation assay published previously (28,63,64).…”
Section: Methodsmentioning
confidence: 96%
“…Cotinine is further metabolized to trans-3′-hydroxycotinine and this reaction is entirely mediated by CYP2A6 [4]. CYP2A6 is also the main enzyme metabolizing therapeutic compounds such as coumarin [5], tegafur [6], and SM-12502 [7], and it can bioactivate tobacco smoke procarcinogens such as N′-nitrosonornicotine (NNN) and 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) [8].…”
Section: Introductionmentioning
confidence: 99%
“…28 Therefore, these data suggest that CYP2B1 is presumedly as one of the major Bicyclol-induced P450 isoform(s) that attributes to the denitrosation of DEN in rat hepatic microsome, but the total spectrum of P450 isoforms after Bicyclol induction differs from the CYP2B1-inducer phenobarbital. So, further study requires using CYP isoform specific antibodies and isoform-specific blockers to clarify if the specific CYP isoform(s) otherwise CYP2B1, like CYP2A6 in previously reported, 59 is correlated to the Bicyclol-induced increase in denitrosation of DEN.…”
Section: Discussionmentioning
confidence: 98%
“…At least three CYP families: 2B, 2A and 2E have been reported as the major CYP genes involved in biotransformation of dialkylnitrosamines, [58][59][60] and are presumedly correlated to Bicyclol inducible P450 activities for DEN metabolism. Shu and Hollenberg indicated that CYP2E1 was one of the P450 isoforms for short chain substrates such as DMN.…”
Section: Discussionmentioning
confidence: 99%